Is gastric cancer part of the tumour spectrum of hereditary non-polyposis colorectal cancer? A molecular genetic study. Issue 7 (31st January 2007) - Gylling, A; Abdel-Rahman, W M; Juhola, M; Nuorva, K; Hautala, E; Järvinen, H J; Mecklin, J-P; Aarnio, M; Peltomäki, P
Abstract : Background: Gastric cancer is the second most common extracolonic malignancy in individuals with hereditary non-polyposis colorectal cancer (HNPCC)/Lynch syndrome. As gastric cancer is relatively common in the general population as well, it is not clear whether or not gastric cancer is a true HNPCC spectrum malignancy. Aim: To determine whether or not gastric cancer is a true HNPCC spectrum malignancy. Subjects and methods: The molecular and clinicopathological profiles of gastric cancers (n = 13) from HNPCC mutation carriers were evaluated and compared with the profiles of sporadic gastric cancers (n = 46) stratified by histology and microsatellite instability (MSI) status. Results: This study on sporadic and HNPCC gastric cancers revealed several important universal associations. Loss of heterozygosity in the adenomatous polyposis coli (APC) region was associated with intestinal histology regardless of the MSI (p = 0.007). KRAS-mutations (p = 0.019) and frameshift mutations in repeat tracts of growth-regulatory genes (p<0.001) were associated with MSI tumours being absent in microsatellite stable (MSS) tumours. The average number of methylated tumour suppressor gene loci among the 24 genes studied (methylation index) was higher in MSI than in MSS tumours regardless of histology (p<0.001). Gastric cancers from HNPCC mutation carriers resembled sporadic intestinal MSI gastric cancers, except that MLH1 promoter methylation was absent (p<0.001) and the general methylation index was lower (p = 0.038), suggesting similar, but not identical, developmental pathways. All these lacked the mismatch repair protein corresponding to the germline mutation and displayed high MSI. Conclusion: The present molecular evidence, combined with the previous demonstration of an increased incidence relative to the general population, justify considering gastric cancers as true HNPCC spectrum malignancies.